Developing a multi-disciplinary program for routine acetylcholine vasoreactivity testing in the cardiac catheterization laboratory. (14th October 2021) - Tran, L; Tuite, M; Michaela Serpa, S; Kunnirickal, S; Esposito, T; Pfau, S E; Shah, S M
Abstract: Background/Introduction: Of the patients who are referred for invasive coronary angiography 30–50% are found to have no obstructive coronary artery disease. Current ESC Guidelines for chronic coronary syndromes have a class IIa recommendation for intracoronary provocative testing with acetylcholine in patients with ischemia and no obstructive coronary artery disease (INOCA). However, there is limited guidance for pharmacy and nursing teams for the support of provocative testing in the cardiac catheterization laboratory. Purpose: To demonstrate feasibility and safety of acetylcholine vasoreactivity testing in the cardiac catheterization laboratory. Methods: The inpatient pharmacy developed an adapted protocol based on available evidence and facilitated a multi-disciplinary operational workflow for the assessment of vasospastic angina. 3mL acetylcholine aliquots of 1mcg/mL, 10 mcg/mL, 25 mcg/mL, 50 mcg/mL, and 100 mcg/mL were prepared by pharmacy following sterile compounding standards. The transition from provider or nursing staff compounding to pharmacy compounding provided quality assurance following United States Pharmacopeia compounding standards for improved sterility and patient safety, especially with a complicated micro-dilution recipe. Pharmacy supported the necessary guidance with optimized clinical decision support in the form of a customized order panel embedded in the electronic health record system and compounding software as another layer of standardization and quality assurance. Syringes were made available to the interventional cardiologist in the cardiac catheterization laboratory suite immediately prior to a scheduled case. Eleven orders of acetylcholine were placed with five dilution syringes per order (total 55 compounded syringes) from the customized acetylcholine provoked coronary vasospasm procedure order panel. Results: From January 2020 to March 2021, 11 patients underwent acetylcholine vasoreactivity testing for clinical indications. One patient developed atrial fibrillation with a rapid ventricular rate during provocative testing of the right coronary artery which required elective cardioversion the following day. Of 11 patients, 9 were outpatients and 2 were inpatients. 1 patient received intravenous atropine and ondansetron due to profound bradycardia and nausea after 100mcg acetylcholine administration. No other safety events occurred. Conclusion(s): Provocative testing with intracoronary acetylcholine administration is safe and feasible. For clinical assessment, sterile compounding and customized order panels facilitate routine clinical assessment for patients with suspected vasospastic angina. Nursing protocols should include cardiac monitoring, medications to reverse adverse effects, and possible outcomes of provocative testing. We provide a practical description of our workflow for pharmacists, catheterization laboratory staff, and providers for routine acetylcholine provocation for the evaluation of INOCA. FUNDunding Acknowledgement: Type of funding sources: None.